Tổng hợp và cấu trúc của một số phức chất trans-dicloro(safrol)(amin thơm)platin (II) - Thanh Chi, Nguyễn Thị; Đà, Trần Thị; Như, Vũ Quang; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
Four complexes of platinum(II) including trans-[Pt(Saf)(o-toludine)Cl2] (P1), trans-[Pt(Saf)(p-toludine)Cl2] (P2), trans-[Pt(Saf)(o-anisidine)Cl2] (P3), trans-[Pt(Saf)(p-anisidine)Cl2] (P4) have been synthesized. The structure of the complexes have been determinded by elemental analysis, molar conductivity, IR, Raman, electronic and 1H-NMR spectra studies